Surgical Management and Post-Operative Outcomes during Anterior Cervical Discectomy and Fusion among Patients presented with Degenerative Cervical Disc Disease attended at a Referral Neuroscience Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Surgical management of degenerative cervical disc disease is very challenging.Objective: The purpose of the present study was to assess the surgical management and post-operative outcomes during anterior cervical discectomy and fusion among patients presented with degenerative cervical disc disease.Methodology: This non-randomized clinical trial was conducted in the Department of Neurosurgery at National Institute of Neurosciences and Hospital Dhaka, Bangladesh from January 2022 to December 2023 for a period of two periods. All the patients with the more than or equal to 18 years of age of both male and female who were presented with degenerative cervical disc disease were selected for this study. Patients were undergoing single- or two-level anterior cervical discectomy and fusion (ACDF) for degenerative cervical disc disease.Results: The mean age was 45.5 ± 15.6 years (range: 19 to 79 years). Majority of the patients were male (87/100). Presenting symptoms were neck pain (79.0%), limb weakness (75.0%), paresthesias (57.0%), radicular pain (47.0%), stiffness in limbs (17.0%), and bladder involvement (15.0%). During discharge, significant improvement in preoperative symptoms were reported like neck pain (61%), stiffness in limbs (81.0%), limb weakness (72.6%), radicular pain (63.0%), paresthesias (83.0%), and bladder symptoms (61.0%). There were several postoperative complications reported like dysphagia (19.0%), hoarseness of voice (29.0%), deterioration of motor power (8.0%), and postoperative hematoma (7.0%).Conclusion: In conclusion most of the patients show remarkable recovery after ACDF who are presented with degenerative cervical disc disease.Journal of National Institute of Neurosciences Bangladesh, July 2024;10(2):98-103